1988
DOI: 10.1111/j.1746-1561.1988.tb05856.x
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Drug Education in Schools: An Analysis of the Costs and Teacher Perceptions

Abstract: This study examined conditions in which two substance abuse prevention curricula were implemented in three Oregon school districts. Data related to teachers' involvement were collected from on-site interviews in 21 schools using a 43-item personal interview questionnaire with a stratified random sample of 44 teachers of drug education. Information provided by district program coordinators included details of inservice training, and financial costs to implement the Here's Looking at You, Two, (HLAY, II) and Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…To the extent that fidelity is seen as a preeminent goal, then teacher discretion must be seen as undesirable, and school district-and school-level authorities should be diligent in stressing the importance of strict adherence to curriculum guides. At the same time, our study and those of others 7,8,59,60 all make it abundantly clear that some degree of curricular adaptation is both widespread and probably inevitable. Some researchers have suggested that it may, in some cases, even be desirable.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…To the extent that fidelity is seen as a preeminent goal, then teacher discretion must be seen as undesirable, and school district-and school-level authorities should be diligent in stressing the importance of strict adherence to curriculum guides. At the same time, our study and those of others 7,8,59,60 all make it abundantly clear that some degree of curricular adaptation is both widespread and probably inevitable. Some researchers have suggested that it may, in some cases, even be desirable.…”
Section: Discussionmentioning
confidence: 65%
“…7 An assessment of the "Here's Looking at You II" prevention curriculum revealed that teachers in one of three school districts studied delivered only half of the number of lessons specified. 8 In another study, Tappe and colleagues 9 found that 84% of teachers omitted at least one module in the Teenage Health Teaching Modules curriculum, and they were less likely to use critical elements of the curriculum such as role-playing and family communication than other elements. In a recent effectiveness trial of "Life Skills Training," Botvin et al 10 found that the mean number of program "points" covered during curriculum delivery was 48%, a percentage that might have been even lower had teachers not been aware that they were under observation.…”
mentioning
confidence: 97%
“…A growing number of prevention programs, particularly in the substance abuse literature, monitored implementation extensively and have shown that variability in the quality of implementation is related to program outcomes (Basch, 1984;Blakely et al, 1987;Botvin, Baker, Dusenbury, Botvin, & Diaz, 1995;Connell, Turner, & Mason, 1985;Hansen, Graham, Wolkenstein, & Lundy, 1989;Gottfredson, Gottfredson, & Hybl, 1993;Rohrbach, Graham, & Hansen, 1993;Ross, Luepker, Nelson, Saavedra, & Hubbard , 1991;Sobol et al, 1989;Taggart, Bush, Zuckerman, & Theiss, 1990;Tricker & Davis, 1988).…”
Section: School-based Implementationmentioning
confidence: 98%
“…For teachers, implementing the interactive techniques and content typical of evidence-based programs can involve considerable difficulty and effort. Moreover, too often, they tend to reinvent, add or subtract elements of the manual to suit their needs or preferences (Tricker, & Davis, 1988;Fagan, & Mihalic, 2003), running the risk of changing the theoretical foundations of the program and the essential nature of the intervention.…”
Section: Introductionmentioning
confidence: 99%